Writing Indian nations : native intellectuals and the politics of historiography, 1827-1863 - Konkle, Maureen (University of North Carolina Press, 2004)
In the early years of the republic, the US government negotiated with Indian nations. This work demonstrates that by depending on treaties, Europeans in North America institutionalized a paradox: the very documents by which they sought to dispossess Native peoples in fact conceded Native autonomy.